Blending polylactic acid with polyhydroxybutyrate: the effect on thermal, mechanical, and biodegradation properties - Min Zhang; Noreen Thomas (2011)
Blends of polylactic acid (PLA) and polyhydroxybutyrate (PHB) at a number of different PLA/PHB weight ratios (100/0, 75/25, 50/50, 25/75, 0/100) have been prepared by melt compounding. The morphology, thermal properties, mechanical properties, and biodegradation behavior of these blends have been investigated. The results indicate that PLA/PHB blends are immiscible but exhibit molecular interaction. PHB is highly crystallizable, and it enhances the recrystallization of PLA and consequently increases the heat distortion temperature. Adding PLA to PHB improves the mechanical properties of PHB. In fact, blending with PHB is also a viable approach to improve the mechanical properties of PLA because the PLA/PHB 75/25 blend exhibits significantly improved tensile properties compared with pure PLA. This is due to the finely dispersed PHB crystals acting as a filler and nucleating agent in PLA. The biodegradability, studied by weight change measurement at room temperature, improved with increasing PHB content.